The Prem sagur - Caturbhujamisra, active 17th century; Hollings, W. (William), 1810-1857; Lallu Lal, 1763-1825 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Prem Sagur" by Caturbhujamisra is a historical text that was popular in the 17th century. This work appears to narrate the events from the Mahabharata and the life of the deity Krishna, detailing the moral and ethical teachings inherent in those stories. The narrative is rich with themes of justice, righteousness, and divine intervention within the human realm. The opening of "The Prem Sagur" introduces the historical context following the great war of the Pandavas, highlighting King Pureechit who encounters a significant moral dilemma involving the manifestations of virtue and sin in society. Witnessing an act of injustice against a cow and a bullock, the king confronts the perpetrator, identifying him as a representation of the Black Age$1 (Ba time characterized by immorality. The king's actions set off a series of events leading to reflection on his own actions and the nature of fate, as he grapples with the consequences of cursing a saint. This sets the stage for a deeper exploration of character, duty, and the teachings of Krishna that will unfold throughout the text. (This is an automatically generated summary.)s
English translation by W. Hollings of Lallu Lal's Hindi translation of the Prem sagur in Braj Bhasha.
Release date is 2024-07-15
an anonymous Project Gutenberg volunteer
Keywords: Krishna (Hindu deity)